Critical Adaptability and Collaboration: A Student Reflection on Preparing for Scholarly Communication Librarianship - Lindsay, Ruby (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2023)
The quickly changing landscape of the scholarly communication ecosystem necessitates critical reflection on the preparedness of students entering this area of librarianship. A literature review of common roles, skills, and competencies of scholarly communication librarians followed by a personal reflection on learning and development as a Master of Library and Information Studies student reveals that collaboration and adaptability are required to succeed in this area.